EMBRACING ASEAN COMMUNITY: MALAYSIA, INDONESIA AND BRUNEI YOUTH PERSPECTIVE - Nurul Huda, Marwan (UNIMAS Publisher, 2017)
After 48 years in existence, ASEAN has eventually transformed from periodic annual meetings of ministers to setting ambitious goals to transform itself into an integrated region; the ASEAN Community by the year 2020. An important tension in this transformation is the question of whether the people of ASEAN are aware and ready to embrace the initiative. As such, this study is interested to discover youths’ awareness, attitudes and expectations toward the establishment. For this purpose, a set of questionnaires has been distributed to a total of 600 university students from Universiti Malaysia Sarawak, Universiti Brunei Darussalam and Universitas Tanjungpura, Kalimantan which act as the aggregate view of youths originating from Borneo. The finding reveals limited familiarity on ASEAN and ASEAN Community among the respondents. Hence, this study implies that a concerted effort should be done in communicating the message of ASEAN Community to the ASEAN masses. Core elements include sufficient exposure on ASEAN Community’s vision and mission, availability of specific mandatory courses on both school and university level and the initiation of more intra-ASEAN exchange programs; strengthening friendships and ensuring eventual steps to a greater consolidated integration. Future expansions to this study could be applied in other universities across the region in order to better gauge the general awareness and readiness of the youth towards the initiative.